2015
DOI: 10.1007/s10522-015-9611-y
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of aging, life span and spontaneous carcinogenesis in the wild type and HER-2 transgenic FVB/N female mice

Abstract: FVB/N wild type and transgenic HER-2/neu FVB/N female mice breed at N.N. Petrov Research Institute of Oncology were under observation until natural death without any special treatment. Age-related dynamics of body weight, food consumption and parameters of carbohydrate and lipid metabolism, level of nitric oxide, malonic dialdehyde, catalase, Cu, Zn-superoxide dismutase, vascular endothelial growth factor were studied in both mice strains. The parameters of life span and tumor pathology were studied as well. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 18 publications
0
7
0
4
Order By: Relevance
“…It is also possible that differences in MMSCs differentiation potential of the studied control mice can be related to strain-dependent features of the functional state of the neuroendocrine system. For example, in FVB/N mice, the level of thyroxine (T4) in the blood is almost three times higher than that of 129/Sv mice, while in rats deficient in T4, the differentiation of MMSCs in the osteogenic direction is strongly inhibited [32,33,34]. It has been shown that melatonin stimulates differentiation of osteoblast precursors, increases osteoblast activity and expression of collagen type 1, osteopontin and osteocalcin [11,35,36].…”
Section: Resultsmentioning
confidence: 99%
“…It is also possible that differences in MMSCs differentiation potential of the studied control mice can be related to strain-dependent features of the functional state of the neuroendocrine system. For example, in FVB/N mice, the level of thyroxine (T4) in the blood is almost three times higher than that of 129/Sv mice, while in rats deficient in T4, the differentiation of MMSCs in the osteogenic direction is strongly inhibited [32,33,34]. It has been shown that melatonin stimulates differentiation of osteoblast precursors, increases osteoblast activity and expression of collagen type 1, osteopontin and osteocalcin [11,35,36].…”
Section: Resultsmentioning
confidence: 99%
“…Petrov National Medical Research Center of Oncology for about 20 years originates from Charles River Laboratories [17]. The female mice, which develop multiple spontaneous mammary adenocarcinomas starting from about 6 months of age, have been extensively used at our laboratory to test the effects of different substances on mammary cancer [18][19][20][21][22][23]. In particular, it has been shown that 1 month of exposure to melatonin alone does not influence tumor growth in 6-month-old mice [17].…”
Section: Methodsmentioning
confidence: 99%
“…Mice were randomized between the groups with the matching mean tumor node volumes. The number of tumors was not controlled, and it ranged from 3 to 6 as multiple tumor nodes developed in the used mouse strain [21]. Exact number of tumors in each study group is indicated in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Петрова» Минздрава России. Эти мыши отличаются значительной частотой развития спонтанных опухолей молочных желез у самок, иногда они возникают и у самцов [7,8].…”
Section: Introductionunclassified